2002
DOI: 10.1186/1471-2458-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation and results of a questionnaire for functional bowel disease in out-patients

Abstract: Background: The aim was to evaluate and validate a bowel disease questionnaire in patients attending an out-patient gastroenterology clinic in Greece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Questionnaires for functional gastrointestinal (GI) disorders, [11][12][13] fecal incontinence and constipation, [14][15][16] or irritable bowel syndrome (IBS) 17,18 have been used to evaluate patients with constipation. However, these measures address upper and lower GI symptoms for functional GI disorders, or both constipation and diarrhea for IBS patients who often have alternating bowel habits.…”
mentioning
confidence: 99%
“…Questionnaires for functional gastrointestinal (GI) disorders, [11][12][13] fecal incontinence and constipation, [14][15][16] or irritable bowel syndrome (IBS) 17,18 have been used to evaluate patients with constipation. However, these measures address upper and lower GI symptoms for functional GI disorders, or both constipation and diarrhea for IBS patients who often have alternating bowel habits.…”
mentioning
confidence: 99%
“…Some articles have demonstrated that in the process of IBS diagnosis GPs consider useful the presence of a long history of disturbances, of unexplained and multiple symptoms, the absence of symptoms during the night, the age of patients, and the presence of a relation between psychological distress and symptoms [11,14,15]. In other words, the GPs consider the absence of alarm features and the presence of signs referable to multiple organs as useful diagnostically.…”
mentioning
confidence: 99%
“…A higher number of publications per PRO were associated with higher quality as subsequent publications assessed quantitative aspects such as longitudinal assessments and minimally important differences. The PROs cover a range of conditions, including achalasia (23), celiac sprue (24,25), dyspepsia (2643), eosinophilic esophagitis (44), fecal incontinence (4560), functional GI disorders (25,41,49,53,6086), gastroesophageal reflux disease (30,38–40,43,87110), GI malignancies (48,77,111115), postgastrectomy (113,116), ileal conduit diversion (117), ileostomy (118), inflammatory bowel disease (119127), pregnancy-related GI symptoms (128130), systemic sclerosis (131133), and radiation enteritis (57), among others. In all, 15 PROs apply to the pediatric population (44,45,60,77,80,97,100,102,115,123,124,134137), and 6 apply specifically to women (56,128130,138,139).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included PROs, 12 included symptoms of abdominal pain (41,44,49,61,63,66,114,131,134,140142). The PROs reveal that abdominal pain is multifaceted; PRO items cover many dimensions of abdominal pain, including intensity, frequency, bothersomeness, location, and pain interference.…”
Section: Resultsmentioning
confidence: 99%